West Africa's security challenges : building peace in a troubled region - Adebajo, Adekeye, 1966-; Rashid, Ismail O. D., 1963- (Boulder : Lynne Rienner Publishers, 2004)
"Among the world's most unstable regions, West Africa in the last decade has experienced a web of conflicts with profound and wide-ranging effects. West Africa's Security Challenges is the first comprehensive assessment of the resulting mix of setbacks and progress." "The authors provide a context for understanding the region's security dilemmas, highlighting the link between failures of economic development, governance, and democratization on the one hand, and military insecurity and violent conflicts on the other. The role of key regional and external actors in foiling - and sometimes fueling - conflicts is also examined. The result is an analysis that is not only academically rigorous, but also relevant to current policy debates."--Jacket.
Introduction / Adekeye Adebajo -- ECOWAS : a retrospective journey / Adebayo Adedeji -- The travails of integration / S.K.B. Asante -- The dilemmas of regionalization / Daniel C. Bach -- Governance and democratization / Amos Sawyer -- The fifth wave of pan-Africanism / Christopher Landsberg -- Civil-military relations / Jimmy D. Kandeh -- Rebel movements / Ibrahim Abdullah, Ismail Rashid -- The political economy of conflict / Eboe Hutchful, Kwesi Aning -- Small arms, light weapons / Comfort Ero, Angela Ndinga-Muvumba -- Children and armed conflict / 'Funmi Olonisakin -- Civil society / Yasmin Jusu-Sheriff -- Pax West Africana? : regional security mechanisms / Adekeye Adebajo -- The United Nations / James O.C. Jonah -- France, Britain, and the United States / Kaye Whiteman, Douglas Yates -- West Africa's post-cold war security challenges / Ismail Rashid.
Includes bibliographical references (pages 401-417) and index.
Keywords: Since 1960; National security -- Africa, West; Regionalism -- Africa, West; Conflict management -- Africa, West; Peace-building -- Africa, West; National security